(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Climate change and flood hazards have been noted as the causes of a 91% decline in agricultural productivity for both crop and livestock farmers. Based on a survey of 80 smallholder farmers, this study offers important insight into how smallholder agricultural farmers are adapting to the effects of climate change and the variables influencing their decisions in Korociriciri Settlement, Fiji. The assessment indicates that to increase productivity, farmers have prioritized factors in their resilience and adaptation strategies by improving the drainage system, changing their planting techniques, practicing seasonal agriculture, increasing the use of targeted pesticides, and switching to organic farming. The socioeconomic characteristics of farmers, such as their age, education level, agricultural experience, landholding capacity, and access to extension and information services, all have a positive, considerable impact on how much they are conscious of climate change. This study suggests a practical route for policymakers and academics to take in order to establish vital plans and studies to offer farmers a range of facilities that might handle diverse climate threats. It is also recommended that mass media and information technologies be used to promote farmers’ knowledge of climate change.